Electronic, magnetic, vibrational, and X-ray spectroscopy of inverse full-Heusler Fe2IrSi alloy. Issue 20 (14th May 2021) - Lalrinkima; Ekuma, C. E.; Chibueze, T. C.; Fomin, L. A.; Malikov, I. V.; Zadeng, L.; Rai, D. P.
Abstract : The electronic, magnetic, structural, vibrational, and X-ray absorption spectroscopy of inverse full-Heusler Fe2 IrSi alloy has been studied from density functional theory (DFT). The XA-phase with FM-configuration is the most stable one, structurally and thermodynamically. Abstract : We report the electronic, magnetic, structural, vibrational, and X-ray absorption spectroscopy of the inverse full-Heusler Fe2 IrSi alloy. We employed state-of-the-art first-principles computational techniques. Our ab initio calculations revealed a ferromagnetic half-metallicity with a magnetic moment of ∼5.01 μ B, which follows the Slater Pauling rule. We show rich magnetic behavior due to spin–orbit coupling through the entanglement of the Fe-3d/Ir-5d orbitals. The large extension of the Ir-5d orbital and the itinerant Fe-3d states enhanced spin–orbit and electron–electron interactions, respectively. The analyses of our results reveal that electron–electron interactions are essential for the proper description of the electronic properties while spin–orbit coupling effects are vital to accurately characterize the X-ray absorption and X-ray magnetic circular dichroism spectra. We estimate the strength of the spin–orbit coupling by comparing the intensity of the white-line features at the L3 and L2 absorption edges. This led to a branching ratio that deviates strongly from the statistical ratio of 2, indicative of strong spin–orbit coupling effects in the inverse full-Heusler Fe2 IrSi alloy.